Study of pregnancy outcome in relation to first trimester body mass index - Srivastava, Prachi; Verma, Hema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Early pregnancy body mass index (BMI) plays an important role in pregnancy outcome. Women with either low or high BMI have an adverse pregnancy outcome. American college of obstetricians and gynecologists (ACOG) recommends calculation of BMI for all pregnant women at their first visit. This study was conducted to assess maternal and fetal outcome in women based on first trimester BMI. Methods: This was a prospective observational study conducted in Department of Obstetrics and Gynecology of T. S. Misra Medical college and hospital, Lucknow from January 2018 to January 2019. Patients with singleton pregnancy booked in first trimester were included while women with multiple pregnancy, pre-existing medical conditions were excluded from the study. Proper history taking and examination was done, and patients divided into five groups as per guidelines of WHO and National Institute of Health Guidelines. Patients were followed up during entire antenatal period. Any maternal and fetal complications were recorded. Results: Incidence of anemia and intrauterine growth restriction (IUGR) was seen more in underweight patients. Postpartum hemorrhage (PIH), gestational diabetes and macrosomia was associated more with patients who were overweight or obese. There was significantly more incidence of lower (uterine) segment caesarean section (LSCS), instrumental delivery, wound sepsis and PPH in patients with higher BMI. SGA babies were seen more in patients with low BMI while large for gestational age (LGA) babies were seen more in patients with high BMI. More neonatal intensive care unit (NICU) admissions were seen in patients with low or high BMI. Conclusions: Complications during pregnancy and adverse pregnancy and neonatal complication was seen significantly more in patients on either side of BMI (underweight and obese). Hence it can be concluded that BMI of a patient directly affects pregnancy outcome.